Effectiveness of an adult food literacy program - Begley, Andrea; Paynter, E.; Butcher, L.; Dhaliwal, Satvinder (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Nutrition education programs aim to improve food literacy domains covering the planning and management, selection, preparation and cooking and eating of healthy food. Reviews indicate programs are effective but acknowledge challenges with evaluation of community focused delivery. Food Sensations ® for Adults (FSA) is a free four-week nutrition and cooking program targeted at low-to-middle income Western Australians who would like to improve their food literacy. The aim of this research was assess how effective FSA is in changing food literacy and selected dietary behaviours. Statistical analysis identified a significant increase in postprogram scores for domains of planning and management, selection and preparation using factor scores (n = 1092). The proportion of the score increase in the postprogram scores compared to the preprogram scores was 10-25%. There was also a significant increase in self-reported fruit and vegetable serve intake, equating to an average increase of ¼ serve/day of fruit and ½ serve/day of vegetables. Of those classified as low food literacy, 61-74% improved postprogram scores in the three domains. FSA is effective in improving food literacy and dietary behaviours and the results add to the evidence base as to how effective these programs can be and for whom they should be targeted for future success.